Heavy metals in bivalves and sediment of Langkawi and Pahang coastal waters, Malaysia - Mohd Zahir bin Md Suhaimi (Kulliyyah of Science, International Islamic University Malaysia, 2011)
A study was conducted in the area of Langkawi and Pahang coastal waters to assess the heavy metal pollution levels in bivalves and sediment samples. A total of 10 species of bivalves and sediment samples were collected from the 13 sampling sites. The sampling was done based on the availability of bivalve‟s species at the sampling sites between January 2009 to January 2010. The majority of sediment samples in the study area (Langkawi and Pahang) were fall in coarse sand to medium silt, sorting ranged from moderately well sorted to very poorly sorted type, skewness of the samples varies from very negatively skewed to very positively skewed, and for kurtosis a majority of the samples falls under very leptokurtic to extremely leptokurtic for both areas. The percentage of organic carbon contents in the sediments were analyzed using the wet dichromate oxidation method while selected heavy metals concentrations were analyzed using Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) after acid digestion using Teflon Bomb method and open digestion. The average concentrations of coastal water organic carbon for Langkawi ranged with the value of 0.84% to 2.8% and Pahang coastal water organic carbon contents ranged with the value of 0.2% to 2.59%. The mean concentration of heavy metal in bivalves and sediment for Langkawi and Pahang coastal water are : for Fe was 85.53 ± 25.23 μg/g dw; 169.40 ± 67.73 μg/g dw; 1.55 ± 0.39 % ; 1.52 ± 0.30 %, for Zn was 86.35 ± 19.88 μg/g dw; 62.24 ± 28.73 μg/g dw; 93.1 ± 29.81 μg/g dw; 73.35 ± 10.98 μg/g dw, for Cu was 9.63 ± 1.94 μg/g dw; 15.00 ± 5.83 μg/g dw; 29.60 ± 8.01 μg/g dw; 21.06 ± 2.32 μg/g dw, for Pb was 0.59 ± 0.24 μg/g dw; 0.28 ± 0.17 μg/g dw; 26.0 ± 7.49 μg/g dw; 26.27 ± 7.73 μg/g dw, for Cd was 1.03 ± 0.26 μg/g dw; 0.23 ± 0.16 μg/g dw; 0.66 ± 0.31 μg/g dw; 0.38 ± 0.12 μg/g dw, for Mn was 74.93 ± 9.55 μg/g dw; 48.25 ± 11.38 μg/g dw; 398.22 ± 135.19 μg/g dw; 328.45 ± 49.22 μg/g dw, for Ni was 2.21 ± 0.62 μg/g dw; 4.19 ± 3.36 μg/g dw; 29.30 ± 9.35 μg/g dw; 37.29 ± 4.79 μg/g dw, and for Cr was 1.20 ± 0.23 μg/g dw; 1.05 ± 0.31 μg/g dw; 55.13 ± 12.32 μg/g dw; 49.06 ± 5.26 μg/g dw respectively. Heavy metal study conducted in Langkawi and Pahang coastal water shows that these areas are not relatively contaminated with the studied heavy metals contents. The concentrations of heavy metals studied seem to be occurring due to the natural processes. This was proved by the evaluation of enrichment levels for those metals which were assessed using Enrichment Factors (EF), and Geoaccumulation Index (Igeo) methods. In all cases, the heavy metals studied in bivalves show that the level is still in the range of permissible limit for human consumption, but a continuous monitoring of heavy metals in bivalves and sediment is needed in order to assess the pollution status at both area, Langkawi and Pahang coastal waters.